2009
DOI: 10.1007/s00330-009-1303-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of 18F-FDG PET/CT in evaluation of early response to neoadjuvant chemotherapy in patients with locally advanced breast cancer

Abstract: We evaluated the role of 18F-FDG PET/CT for the assessment of response after two cycles of neo-adjuvant chemotherapy (NACT) for breast cancer. Twenty-three women with locally advanced breast cancer were included in this study. Early response to NACT was evaluated after two cycles using clinical examination, CT, and 18F-FDG PET/CT. Final histopathology following surgery after six cycles of NACT served as reference. Baseline PET/CT demonstrated a total of 26 lesions in 23 patients. The size of the primary tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 28 publications
3
58
3
Order By: Relevance
“…Several studies that examined a possible role for metabolic evaluation with 18 F-FDG PET have evidenced a correlation between early changes in the maximum standardized uptake value (SUV max ) (after one or two courses of chemotherapy) and the final pathological response after completion of NAC [6][7][8][9][10][11][12][13][14]. However, the ability to implement early 18 F-FDG PET as a surrogate marker for treatment efficacy in clinical practice remains unclear because of substantial heterogeneity across studies.…”
mentioning
confidence: 99%
“…Several studies that examined a possible role for metabolic evaluation with 18 F-FDG PET have evidenced a correlation between early changes in the maximum standardized uptake value (SUV max ) (after one or two courses of chemotherapy) and the final pathological response after completion of NAC [6][7][8][9][10][11][12][13][14]. However, the ability to implement early 18 F-FDG PET as a surrogate marker for treatment efficacy in clinical practice remains unclear because of substantial heterogeneity across studies.…”
mentioning
confidence: 99%
“…A correlation has been demonstrated between early changes in the maximum standardized up take value (after one or two courses of chemother apy) and the final treatment response at the com pletion of NAC [13][14][15]. Relative changes in both the maximum standardized uptake value (SUV max) and standardized uptake value (SUV) have been proposed as a means to discriminate meta bolic responders from nonresponders or to differ entiate between pathological complete response (pCR) and nonpCR [13][14][15].…”
Section: Assessment Of Response To Therapymentioning
confidence: 99%
“…Relative changes in both the maximum standardized uptake value (SUV max) and standardized uptake value (SUV) have been proposed as a means to discriminate meta bolic responders from nonresponders or to differ entiate between pathological complete response (pCR) and nonpCR [13][14][15]. Recently, a study by Andrade et al demonstrated that the optimal per centage change in posttreatment SUV scores rel ative to baseline (ΔSUV) to discriminates between pCR and nonpCR was -71.8% (83.3% sensitivi ty; 78.5% specificity); the optimal ΔSUV thresh old to discriminate between NAC responders and nonresponders was -59.1% (68% sensitivity; 75.0% specificity) [16].…”
Section: Assessment Of Response To Therapymentioning
confidence: 99%
“…In many studies [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] that have evaluated a possible role for metabolic evaluation with FDG-PET and PET/ CT, investigators demonstrated a correlation between early changes in FDG uptake, mostly in terms of the SUV max value, after one or two courses of chemotherapy and the final pathologic response upon completion of chemotherapy, or patient outcome (Table 4). A review article including 745 patients in 15 studies indicated that the pooled sensitivity and specificity of FDG-PET for early separation of responders from non-responders could reach 80.5 % (95 % CI, 75.9-84.5 %) and 78.8 % (95 % CI, 74.1-83.0 %), respectively [91].…”
Section: Early Treatment Response Assessmentmentioning
confidence: 99%